Peak metamorphic temperatures acquired through Raman Spectroscopy on Carbonaceous Material (RSCM) from the Northern Range, Trinidad - Ivano Gennaro; Xu Chu; Alberto Vitale Brovarone; John C Weber; Jeanette Arkle (PANGAEA, 2021)
The Northern Range of Trinidad is a mountain range located along the northern Trinidadian coast formed through the oblique collision between the Caribbean and South American plates in the Oligocene and Miocene. Previous geothermometric attempts at characterizing the peak metamorphic temperatures across the Northern Range yielded results with large associated errors due to the low metamorphic grade and a lack of suitable index minerals. In order to better constrain the peak metamorphic temperatures across the Northern Range, as well as to investigate the presence and continuity of a previously described thermal gradient, we employ Raman spectroscopy on carbonaceous materials (RSCM), utilizing multiple calibrations to cover the range of peak temperatures in the area. Data were collected in 2019 using Raman spectrometers at the University of Torino (UNITO) in Italy and the Royal Ontario Museum (ROM) in Canada on 26 samples made from a variety of lithologies from across the Northern Range. Spectra were acquired from standard petrographic thin sections using a 532 nm laser at low power to avoid within-sample heating, with the analyzed carbonaceous material (CM) being hosted beneath transparent minerals to avoid the effects of sample preparation on the CM crystal structure. 3-4 accumulations of 15 seconds were collected for each CM grain in the range of 700-2000 cm^-1, with at least 15 spectra being collected for each of the 26 samples. Raman spectra were fit using the PeakFit software in accordance with the calibrations used (Beyssac et al., 2003; Aoya et al., 2010; Lahfid et al., 2010; Kouketsu et al., 2014 ); temperatures were then calculated using the relevant band parameters and are reported in this dataset along with the relevant calibration. This dataset provides information on the location, wellness of fit, spectrometer used, fitted band parameters, RSCM calibration, and calculated RSCM temperature for each sample analyzed from the Northern Range.